Mastery of Religious and Heroic Values in the Drama Script Pattimura by Farid Latif in Drama Learning for VIII Grade Students at State Junior High School 7 Ambon - Angwarmase, Kristina; Lewier, Mariana; Rumalean, Iwan (Universitas Pattimura, 2022)
Drama learning is one of the materials presented in literature learning at the junior high school level. However, in reality, there are still several obstacles that need to be considered by educators and for which solutions need to be found. The problem observed in this study relates to the mastery of life values in drama scripts and is found in SMP Negeri 7 Ambon, 7th grade. This study is quantitative descriptive, focusing on the mastery of religious and heroic values in the drama script